Supporting clinical processes with semantic web technologies: a case in breast cancer treatment. (1st October 2010) - Serna Nocedal, Ainhoa; Gerrikagoitia, Jon Kepa; Huerga, Iker
Breast cancer surgery is carried out almost entirely manually and there is an obvious risk of human error due to temporary or occasional lack of staff experience (substitutions, sick leaves and other reasons). Another aspect is that the successful outcome of the process may depend on the personal attitude of administrative staff. In order to guarantee patient safety the whole process should be orchestrated and monitored automatically. Support for the solution will be a service-oriented architecture combined with semantic web techniques to infer knowledge from predefined rules in order to make the process safe.